Economics and Demography: A Review of the Empirical Literature - Kostov, Lyuboslav (Research Papers, 2024)
A review of the contemporary empirical literature on the impact of demographics on economic performance is made. From the empirical review, it is clear that demographic processes and productivity are the two most important factors explaining the growth of per capita income. The impact of population growth on economic growth includes both negative and positive aspects, and these effects change over time and are different in the short and long term. An example of a good economic policy is investing in human capital, which would increase labor productivity and help mitigate the negative effects of certain dynamics of demographic indicators.
Keywords: Demography; Economic growth; Human capital